1974
DOI: 10.1042/bj1440189
|View full text |Cite
|
Sign up to set email alerts
|

Urate synthesis in the perfused chick liver

Abstract: Urate synthesis was studied in a perfused chicken liver preparation. The perfused liver had an ATP/ADP ratio of 0.29+/-0.05(6) compared with 0.34+/-0.07(10) in liver obtained from chicks under ether anaesthesia. Lactate/pyruvate ratios were 9.4+/-1.7(5) in the perfused liver and 14.8+/-1.8(5) in the rapidly sampled liver. Urate synthesis was only marginally stimulated by glycine, glutamine, aspartic acid or NH(4)Cl, but significant increases were observed with phosphoribosyl pyrophosphate, aminoimidazolecarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1975
1975
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The rates in the present experiments were considerably higher than those found with chicken liver slices (Benzinger & Krebs, 1933), but of the same order as the rate of hypoxanthine synthesis under optimum conditions in pigeon liver (Orstrom et al, 1939) and about twice as high as that observed in perfused chicken liver (Barratt et al, 1974 Effect ofNH4CI on chicken liver metabolism When NH4C1 was the only added nitrogenous precursor the rates of urate synthesis were lower than in the presence of alanine or asparagine, with either lactate or dihydroxyacetone as carbon source (Table 5). In the presence of lactate the rates of urate synthesis were lower at 5 mM-and lOmM-NH4CI than at 1 mm.…”
Section: Preparation Of Isolated Liver Cells and Incubation Conditionsmentioning
confidence: 48%
See 3 more Smart Citations
“…The rates in the present experiments were considerably higher than those found with chicken liver slices (Benzinger & Krebs, 1933), but of the same order as the rate of hypoxanthine synthesis under optimum conditions in pigeon liver (Orstrom et al, 1939) and about twice as high as that observed in perfused chicken liver (Barratt et al, 1974 Effect ofNH4CI on chicken liver metabolism When NH4C1 was the only added nitrogenous precursor the rates of urate synthesis were lower than in the presence of alanine or asparagine, with either lactate or dihydroxyacetone as carbon source (Table 5). In the presence of lactate the rates of urate synthesis were lower at 5 mM-and lOmM-NH4CI than at 1 mm.…”
Section: Preparation Of Isolated Liver Cells and Incubation Conditionsmentioning
confidence: 48%
“…The liver outflow was returned to the reservoir by a roller pump. Soling et al (1973) and Barratt et al (1974) perfused the avian liver by the portal vein. Perfusion in the reverse direction was preferred because it made it possible to shorten the anoxic period of the liver.…”
Section: Preparation Of Isolated Liver Cells and Incubation Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modified operative technique for perfusion of the isolated chicken liver A method of operating on the chicken is described which makes it possible to perfuse the isolated liver. It is based on the techniques described by BICKERSTAFFE et al 1970 andBARRATT et al (1974). The authors' experiences have resulted in modifications of the technique in some respects which result in simplifying the operative procedure, carrying it out more rapidly, and obtaining more rapid attachment to the perfusion apparatus.…”
Section: Discussionmentioning
confidence: 99%